Endoparasite and Microbial Burden in Quail Farm Systems: A Biosecurity and Water Quality Assessment in Central Java, Indonesia - Murwani, R.; Dewi, B. P. A.; Anggraeni, R.; Mulyono, M.; Ambariyanto, A. (Tropical Animal Science Journal, 2025)
Quail farming is vital for smallholder farmers in Central Java, Indonesia; however, productivity often declines due to poor biosecurity, inadequate water quality, and parasitic infections. This study aims to examine biosecurity practices, water quality, and endoparasite loads in ten quail farms (L1-L10) located in Semarang City and nearby regencies. Data were collected through observations, interviews, water sampling, and analysis of quail droppings. Biosecurity scores (maximum 18) were categorized into three groups: Group-1 (scores 13-18), Group-2 (scores 7-12), and Group-3 (scores 1-6). Water quality was assessed based on pH, E. coli, and coliform counts using triplicate samples from each site. The biosecurity score showed that three farms are in Group-1 (L1, L7, L9), five are in Group-2, and two are in Group-3 (L8, L10). The water pH ranged from 4.8 to 8.0; the highest E. coli count was 19.33 CFU/mL (L9), and the highest Coliform count was 89.67 CFU/mL (L5). L1 had the highest parasite load, with Coccidia, Strongyloides, and Ascaridia sp. at 1000 oocysts/g (OPG), 100 OPG, and 33.33 OPG, respectively. Meanwhile, L7 showed no endoparasites or water contamination. Egg production ranged from 64.29% to 90.00%. Although no significant differences in endoparasite prevalence were found among biosecurity groups or water quality (p>0.05), Coliform levels differed significantly (p<0.05), with the highest levels in conventional well-water. This study revealed that only about one-third of smallholder quail farms in Semarang and its surrounding regencies adhere to proper biosecurity measures. It was also the first to document quail endoparasite burdens as well as E. coli and coliform contamination in drinking water.